Theoretical-methodological proposal for the study of the government of the citizen participation on the local level established by the Constitution of 2008. - Alvear Morales, César (SATHIRI, 2020)
This theoretical-methodological article comes from a larger study aimed at analyzing, through Focault’s governmentality approach, how government of citizen participation in the Cotacachi canton was produced after the 2008 Constitution came into force. This article arises from the need to generate a methodological proposal that makes possible the study and visibility of the diversity of power dynamics that occur between the different social and state actors in the construction of the cantonal participatory system. The methodological proposal was elaborated first by establishing a theoretical scaffolding of Foucault’s governmentality that supports the methodology under construction, followed by the definition of the study dimensions that the methodology must consider and ending with the determination of the components to be analyzed within of each dimension. Through the bibliographic review and analysis supported by the observations made in a qualitative profile field study, the proposed study methodology was developed.
Keywords: Citizen participation; government, power; governmentality